Gender equity in academic rheumatology: is there a gender gap at European rheumatology conferences? - Hassan, N; van Mens, L; Kiltz, U; Andreoli, L; Delgado-Beltran, C; Ovseiko, PV; Gossec, L; Coates, LC (BMJ Publishing Group, 2022)
Objectives: To obtain an overview of gender equity at European rheumatology conferences. Methods: The proportion of women invited as either moderators or speakers to the European Alliance of Associations for Rheumatology (EULAR) annual congresses and national conferences in Europe was calculated from the published congress materials from EULAR annual congresses (2015-2019) and the 2019 national conferences of France, Germany, Italy, Spain and the UK. Data from EULAR congresses were further categorized by type of session. Significance testing was conducted using chi-squared tests with the level of statistical significance set at p<0.05. Results: The proportion of combined women moderators and speakers at EULAR varied from 40-43% between 2015 and 2019 with no obvious trend over time. There were higher proportions of women in the Health Professionals in Rheumatology and People with Arthritis and Rheumatism sessions (>50% consistently). However, these sessions represent <25% of EULAR congress invitations. Representation of women at the EULAR congress in 2019 (39.6%) was significantly higher than at the national congresses in France (28.6%) and Germany (29.6%) but similar to that observed in Italy (33.7%), Spain (41.7%) and the UK (42%). Conclusion: Women account for less than half of invited moderators and speakers at the conferences reviewed. Compared to historical EULAR data in 2003 (16%) and in 2004 (19%), the gender gap at EULAR congresses has narrowed considerably, but there remains a need to monitor and improve women’s representation.